Synthesis and characterization of SO42-/KCC-1 catalyst as an alternative candidate for simultaneous esterification and transesterification reactions - Ginda Putri Farikhah; Wirda Udaibah; Mulyatun Mulyatun (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2021)
Sulfate-impregnated acid catalysts can be used to replace conventional homogeneous base catalysts which are very dangerous, corrosive and environmentally unfriendly. Sulfate impregnation on porous support material will increase the surface area of the catalyst. The use of KCC-1 as a supporting material can produce catalysts with excellent properties. The method used in this research is the hydrothermal method for the synthesis of KCC-1 and the direct impregnation method for the synthesis of SO42-/KCC-1. Characterization of the resulting material using X-ray diffraction (XRD), FTIR spectrometer, and low temperature emission scanning electron microscope (SEM). The characterization results showed that the synthesis of KCC-1 and SO42-/KCC-1 had been successfully carried out. This is evidenced by the formation of amorphous silica, the presence of peaks of silica and sulfate groups, and scanning electron microscope images showing nano-sized materials.©2021 JNSMR UIN Walisongo. All rights reserved.